Investigating the Association between Preflap Negative-Pressure Wound Therapy and Surgical Outcomes in Extremity Free Flap Reconstruction: A Systematic Review - Rocks, Madeline C.; Wu, Meagan; Comunale, Victoria; Agrawal, Nikhil; Nicholas, Rebecca S.; Azad, Ali; Hacquebord, Jacques H. (Journal of Reconstructive Microsurgery, 2024)
Background While prior studies have recommended immediate flap coverage within 72 hours of injury for soft tissue reconstruction for traumatic extremity injuries, recent evidence in the setting of advanced wound care techniques de-emphasizes the need for immediate coverage. Negative-pressure wound therapy (NPWT) has been an essential tool for extending the time to definitive soft tissue coverage. This study sought to elucidate the impact of preoperative NPWT use on the success of microsurgical reconstruction.Methods A literature search was conducted using the following databases from their inception up to February 2023: PubMed, OVID databases (Embase and Cochrane Library), Web of Science, and Scopus. Of 801 identified articles, 648 were assessed and 24 were included. Cases were divided based on whether NPWT was used preoperatively or not. Timing to definitive coverage, injury details, and basic demographics were recorded. Rates of flap failure, infection, bone nonunion, reoperation, and complications were compared between groups.Results A total of 1,027 patients and 1,047 flaps were included, of which 894 (85.39%) received preflap NPWT. The average time to definitive coverage for the NPWT and non-NPWT groups was 16 and 18 days, respectively. The NPWT group experienced lower postoperative complication rates than the non-NPWT group in all reported complications except for deep infections. Compared with the non-NPWT group, the NPWT group experienced lower rates of any flap failure (3.69 vs. 9.80%) and partial flap failure (2.24 vs. 6.54%).Conclusion Preoperative NPWT was associated with reduced postoperative complications, most importantly flap failure rates. This merits further investigation into the decision-making process for traumatic extremity reconstruction. Future prospective studies adopting standardized protocols with longer follow-up are required to better understand the potentially beneficial role of preoperative NPWT use in soft tissue reconstruction.
Keywords: soft tissue reconstruction; extremity trauma; negative-pressure wound therapy; systematic review